"Entangled Freedom": Ethical Authority, Original Sin, and Choice in Kierkegaard’s Concept of Anxiety - Davenport, John J. (KIERKEGAARDIANA, 2000)
"Entangled Freedom": Ethical Authority, Original Sin, and Choice in Kierkegaard’s Concept of Anxiety